Orientalism in Joseph Conrad’s novel Almayer’s Folly (1895): a post-colonial approach - Iqbal, Muhammad (Universitas Ahmad Dahlan, 2020)
He represents the false critic toward colonialism which depicted him as the author in the neutral side in the history of colonialism. In this undergraduate thesis, the writer attempts to reveal the pattern of Joseph Conrad’s Orientalism by find the image and stereotype of the Orient and Occident, the Fantasy of Western colonialism, the hegemony that legitimate the colonial authorities toward the Malay Archipelago and finds the evidence that proves him as the part of author who supports colonialism. The writer uses Edward’s Said Orientalism theory as the major post-colonial theory in this study to investigate the pattern of Orientalism and the evidence of Joseph Conrad as the colonialist author. The writer uses the technique of writing this undergraduate thesis by dividing the extrinsic and intrinsic element of the novel Almayer’s Folly (1895). In the finding and discussion of this undergraduate thesis, the writer reveals the pattern of Orientalism and the evidence of Joseph Conrad as the pro-colonialism author through the binary division in the novel which creates the stereotype of the Orient and compares to the ideal Victorian character depicted in his white characters in the novel. Then, Conrad creates the Western Fantasy toward the Oriental Malay Archipelago as the object for the Westerner in search of adventure, career and positioning the imaginary narrative of European territory as the happy land for the major characters.